Dopaminergic regulation of inflammation and immunity in Parkinson's disease: friend or foe? - Furgiuele, Alessia (2023)
Parkinson's disease (PD) is a neurodegenerative disease affecting 7-10 million people worldwide. Currently, there is no treatment available to prevent or delay PD progression, partially due to the limited understanding of the pathological events which lead to the death of dopaminergic neurons in the substantia nigra in the brain, which is known to be the cause of PD symptoms. The current available treatments aim at compensating dopamine (DA) deficiency in the brain using its precursor levodopa, dopaminergic agonists and some indirect dopaminergic agents. The immune system is emerging as a critical player in PD. Therefore, immune-based approaches have recently been proposed to be used as potential antiparkinsonian agents. It has been well-known that dopaminergic pathways play a significant role in regulating immune responses in the brain. Although dopaminergic agents are the primary antiparkinsonian treatments, their immune regulatory effect has yet to be fully understood. The present review summarises the current available evidence of the immune regulatory effects of DA and its mimics and discusses dopaminergic agents as antiparkinsonian drugs. Based on the current understanding of their involvement in the regulation of neuroinflammation in PD, we propose that targeting immune pathways involved in PD pathology could offer a better treatment outcome for PD patients.